The Effectiveness of Simulator Learning Media in Learning Motorcycle Charging Systems at Vocational High Schools - Rohayati, Rohayati; Qudus, Nur; Widjanarko, Dwi (Universitas Negeri Semarang, 2025)
The learning process of the motorcycle charging system at SMK Negeri Situraja still faces challenges, notably the low competency mastery of students who have not yet met the Minimum Competency Criteria. This issue arises from the limited time available for practical activities and the lack of varied and contextual teaching methods. This study aims to assess the effectiveness of the learning media, specifically a charging system simulator developed using the Project-Based Learning (PjBL) approach. The research method employed is Research and Development (R&D) with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research results demonstrate that the developed simulator media is effective in improving students competency, particularly in understanding the operating principles and components of the charging system. This effectiveness is indicated by a significant improvement in learning outcomes after the simulator-based instruction. Additionally, students became more active, gained a deeper understanding of the material, and were able to apply the knowledge in independent and safe practices. The advantage of this media, compared to previous studies, is the security system that protects students during use. This feature ensures safety and creates a secure learning environment. Therefore, the PjBL-based simulator media is a suitable innovation for learning in vocational schools to support the achievement of optimal learning outcomes.